Perímetro cervical asociado a riesgo cardiovascular alto en adultos con Diabetes mellitus tipo 2 - Zúñiga Luna, Luis Jhoel (2020)
Objective: To identify if association exists between cervical perimeter and the cardiovascular high risk in patients with diabetes mellitus type 2. Material and methods: Analytical observational study of cases and controls in patients with type 2 diabetes mellitus attended in outpatient internal medicine of the Hospital Regional Docente de Trujillo period January-April of 2018; the cervical perimeter of the patients was measured and the cardiovascular risk was calculated by the Framingham score. This association was analyzed with Chi-square test with a significance level of 5%, and OR (odds ratio) to determine the strength of association. Results: The high cervical perimeter was more frequent in women (80,5%) than in males (19,5%). The high cardiovascular risk was significantly more frequent in women (63,5%) in comparison to the males (36,5%). There was no significant statistically association between both variables (p = 0.709, OR: 1.15, 95% CI [0.55-2.39]). Conclusion: No significant association was found between cervical perimeter and cardiovascular risk in patients with type 2 diabetes mellitus.